Development of Keratinocyte Cell Lines Containing Extrachromosomal Human Papillomavirus Genomes. Issue 9 (8th September 2021) - Coursey, Tami L.; McBride, Alison A.
Abstract: Human papillomaviruses (HPVs) cause persistent infections in stratified cutaneous and mucosal epithelia. In these infections, the viral DNA replicates as low‐copy‐number, extrachromosomal, double‐stranded‐DNA circular plasmids in the nucleus of the dividing basal cells. When the infected cells begin the process of differentiation, the viral DNA amplifies to a high copy number and virions are assembled in the superficial cells. To study HPV DNA replication, our laboratory generates primary keratinocyte cell lines that contain replicating extrachromosomal HPV genomes. Here, we describe protocols to culture human keratinocytes, to transfect viral DNA into cells using electroporation, to determine the efficiency of genome establishment in cells with a colony‐forming assay, and to measure the copy number and extrachromosomal status of viral genomes using Southern blotting. These methods can be used to study DNA replication of different oncogenic Alphapapillomavirus HPV types. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Electroporation to transfect keratinocytes with recircularized HPV genomes Alternate Protocol : Use of HPV replicon containing selection marker in keratinocyte transfection Support Protocol 1 : Rheinwald‐Green method of co‐culture of irradiated J2 3T3 feeders and human keratinocytes Support Protocol 2 : Recircularization of HPV genomes Basic Protocol 2 : Quantitative colony formation assay to measure the efficiency of HPV genome establishment Basic Protocol 3 : Southern blot analysis of extrachromosomal viral DNA Support Protocol 3 : Hirt extraction of low‐molecular‐weight DNA Support Protocol 4 : Qiagen DNeasy Blood & Tissue DNA extraction Support Protocol 5 : Generation of a 32 P‐labeled HPV DNA probe